Upaya Meningkatkan Kemampuan Membaca Permulaan Melalui Permainan Kartu Bergambar Pada Anak Kelompok B TK Pertiwi I Karangjati Kecamatan Blora Kabupaten Blora Tahun Ajaran 2015/2016 - Supriyati, Wiji, Drs. Sutan Syahrir Zabda, SH,MH (2015)
The objective of this study is to increase basic- reading ability group B kindergarten Pertiwi I Karangjati Blora regency school year 2015/2016. This is a classroom action research. Subject of this classroom action research is class B kindergarten Pertiwi I Karangjati totaling 21 children. This study is collaboration between the researcher, teacher and headmaster. Data of this study are collected through observation, questioner and field note. The data analysis of this study uses achievement target percentage. And to check the data validity uses triangulation source. The result of this study shows that: students learning ability is increased after being conducted learning model uses drawing card. Before being conducted classroom action research, children basic-reading ability is 40%. After having approved activity using drawing card game at children reading - learning process got the result: first cycle reaches 50% and second cycle increases to 80%. The result of this study has reached the indicator achievement. Based on the result of this classroom action research the writer's hypothesis says " By using drawing card game is able to increase basic- reading ability at children group B kindergarten Pertiwi I Karangjati Blora, school year 2015/2016", proved and acceptable.